Visible-light-mediated regioselective synthesis of novel thiazolo[3, 2-b][1, 2, 4]triazoles: advantageous synthetic application of aqueous conditions. Issue 3 (6th January 2022) - Aggarwal, Ranjana; Hooda, Mona; Kumar, Prince; Torralba, Mari Carmen
Abstract : A regioselective synthesis of novel thiazolo[3, 2- b ][1, 2, 4]triazoles has been established via a visible-light-facilitated reaction of unsymmetrical α-bromodiketones with 3-mercapto[1, 2, 4]triazoles under aqueous conditions. Abstract : From a green chemistry perspective, sustainable irradiation as the power source and water as the solvent have certainly grabbed the attention of chemists in recent times because their use helps reduce the hazardous ecological footprints of organic synthesis. In the present work, we have established an efficient, straightforward and green protocol for the regioselective synthesis of novel functionalized thiazolo[3, 2- b ][1, 2, 4]triazoles. The visible-light-mediated catalyst-free reaction of diversely substituted α-bromodiketones, generated in situ by the reaction of NBS and 1, 3-diketones, with 3-mercapto[1, 2, 4]triazoles under aqueous conditions afforded thiazolo[3, 2- b ][1, 2, 4]triazole derivatives in excellent yields. The structure of the regioisomer has been confirmed explicitly by heteronuclear 2D-NMR [( 1 H– 13 C) HMBC, ( 1 H– 13 C) HMQC] spectroscopic and X-ray crystallographic studies. Radical initiating and trapping experiments supported the free radical mechanism for the cyclization.